Short flap rhytidectomy and fractional CO2 laser rejuvenation of the aging face. (26th February 2013) - Taghizadeh, Farhan; Leibowitz, Alicia; Ellison, Timothy; Griego, Michael; Traylor‐Knowles, Mimi; Ramirez, Patrick
Summary Background There is currently a high demand for a concurrent system of skin rejuvenation accompanying rhtidectomy. CO2 laser treatment prior to surgical ablative reduction has produced promising results, but the adjunct service of laser treatment at the time of surgery has never been reviewed. Objectives Determine the effects of concurrent treatment of rhytides and evidence of aging in the skin with surgical correction followed by fractional CO2 laser application. Methods During study time from September 2008 to February 2009 treat patients who have underwent short flap rhytidectomy to the Lutronic eCO2™ fractional laser using the patented "Controlled Chaos Technology." Results Complications included 2.3% herpes simplex outbreak, 4% persistent erythema past 2 weeks, four cases of prolonged edema to 5 days, one case of impetigo, and no evidence of dyspigmentation. Patient satisfaction data demonstrated no refunds at 12 months. Conclusions Combination fractional laser resurfacing with short flap, high‐Superficial muscular aponeurotic system rhytidectomy is a safe procedure with excellent patient satisfaction and clinical outcomes.